Ontological MobiHealth System - Nasim Khozouie; Faranak Fotouhi-Ghazvini; Behrouz Minaei-Bidgoli (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
MobiHealth systems are tele-monitoring systems based on BAN (Body Area Network) and mobile health care (m-health) service platform utilizing next generation public wireless networks.  Smart phone applications have self-monitoring and sensing capabilities and are used in health interventions and disease prevention. In this study, a prototype mobile sensing platform was introduced for m-Health and telemedicine applications, which medical sensors on patient body reports biological signals and environmental sensors send environment raw data to base station (smart phone). Then raw data were preprocessed and necessary features (situations) were extracted. In order to context computation and respond with adaptability, we have used ontology-based model.